2016
DOI: 10.1080/15287394.2016.1190675
|View full text |Cite
|
Sign up to set email alerts
|

Antimutagenic and antioxidant properties of the aqueous extracts of organic and conventional grapevineVitis labruscacv. Isabella leaves in V79 cells

Abstract: Grapes are one of the most commonly consumed fruit, in both fresh and processed forms; however, a significant amount is disposed of in the environment. Searching for a use of this waste, the antigenotoxic, antimutagenic, and antioxidant activities of aqueous extracts from organic and conventional Vitis labrusca leaves were determined using V79 cells as model. The antigenotoxic activity was analyzed by the alkaline comet assay using endonuclease III and formamidopyrimidine DNA glycosylase enzymes. The antimutag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…Considering the widespread popular use of extract from aerial parts of C. oxyacantha, and lack of studies specifically assessing the genetic toxic potential of fruit extract, this investigation was conducted to determine the cytotoxic, genotoxic, and clastogenic/aneugenic potential in vitro, using human leukocytes and HepG2 cells, as well as mutagenic potential in bacteria cells. Among the available safety tests, the micronucleus (MN) test, comet assay, and Ames test are recommended by international regulatory agencies for toxicological evaluation of natural products (Choy, 2001;Claxton et al, 2010;OECD 489, 2014;Franco et al, 2015;Trindade et al, 2016). Thus, these tests were utilized to determine the safety of C. oxyacantha.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the widespread popular use of extract from aerial parts of C. oxyacantha, and lack of studies specifically assessing the genetic toxic potential of fruit extract, this investigation was conducted to determine the cytotoxic, genotoxic, and clastogenic/aneugenic potential in vitro, using human leukocytes and HepG2 cells, as well as mutagenic potential in bacteria cells. Among the available safety tests, the micronucleus (MN) test, comet assay, and Ames test are recommended by international regulatory agencies for toxicological evaluation of natural products (Choy, 2001;Claxton et al, 2010;OECD 489, 2014;Franco et al, 2015;Trindade et al, 2016). Thus, these tests were utilized to determine the safety of C. oxyacantha.…”
Section: Introductionmentioning
confidence: 99%
“…Dani et al () reported that total phenolic and flavonoid contents of grape leaves were between 19 and 20.2 mg gallic acid/ml; 7.94 and 8.95 μg rutin/ml, respectively. In the study of Trindade et al (), total polyphenol amount of grape leaf extract ranged from 28.93 to 56.05 mg/g. In another study, total phenolic and flavonoid contents of vine leaves varied from 152.06 to 178.99 mg GAE/g and from 65.10 to 81.99 mg rutin/g, respectively (Koşar et al, ).…”
Section: Resultsmentioning
confidence: 96%
“…Grapes are significant source of polyphenols and antioxidants in leaf, skin, pulp, and seed (Farhadi, Esmaeilzadeh, Hatami, Forough, & Molaie, ). Vitis genus, Vitis labrusca and Vitis vinifera species are generally cultivated vines in all around the world (Trindade et al, ). Grape products such as grape juice or wine are not convenient for diabetic patient or alcoholics because of carbohydrate and alcohol contents, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The comet assay or single cell gel electrophoresis (SCGE) is a simple, quick, and sensitive method for quantitatively measuring DNA strand breaks in individual cells. For the last two decades, this method has been extensively employed in biomonitoring studies and in a range of in vivo and in vitro systems (Cemeli & Anderson, 2011;Dusinska & Collins, 2008;Ferreira et al, 2016;Trindade et al, 2016). Cells with increased DNA damage display enhanced DNA migration from the nucleus toward the anode (Dusinska & Collins, 2008).…”
Section: Introductionmentioning
confidence: 99%